Electrodes for proton-conducting ceramic fuel cells and methods for manufacturing the same
Patent Information
- Application Number
- JP2025058429
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
Smart Images

Figure 2026165825000001_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a method for manufacturing an electrode of a proton-conductive ceramic fuel cell. The present disclosure also relates to an inkjet ink for manufacturing the electrode of the proton-conductive ceramic fuel cell. The present disclosure further relates to an electrode of a proton-conductive ceramic fuel cell including an intermediate layer formed by ejecting the inkjet ink.
Background Art
[0002] Fuel cells have high efficiency because they directly convert chemical energy into electricity. In addition, fuel cells are clean power generation devices that extract electric power from hydrogen and oxygen through a chemical reaction and discharge water. Therefore, practical application of fuel cells has been promoted. Examples of fuel cells include solid oxide fuel cells (SOFC) in which the electrolyte is composed of a ceramic material. Compared with conventional SOFCs, proton-conductive ceramic fuel cells (PCFC) that have higher energy efficiency and can operate at low temperatures have attracted attention.
[0003] PCFC uses protons (H as charge carriers + ) to conduct electricity and generates water vapor on the air electrode side. For this reason, in PCFC, the fuel is not diluted, and the fuel efficiency is high. In addition, PCFC has low activation energy for proton conduction. Therefore, compared with SOFC, PCFC can operate at lower temperatures.
[0004] For example, Japanese Patent Publication No. 2023-006322 discloses an electrode for a proton-conducting ceramic cell, a proton-conducting ceramic cell using the same, and a method for manufacturing the same. The electrode for the proton-conducting ceramic cell is formed of an electronically conductive material and a proton-conducting material containing barium (Ba). The mass ratio of the electronically conductive material to the proton-conducting material is 100:0 to 20:80. In addition, the film thickness of the electrode is 7.0 μm or less. The porosity of the electrode is 20.0 volume% or less. Because the mass ratio, film thickness, and porosity are within the above ranges, the contact points between the electronically conductive material and the proton-conducting material increase. This suggests that the reaction field within the electrode is expanded, the electrode resistance is reduced, and the current density is increased.
[0005] Japanese Patent Publication No. 2024-074357 discloses an air electrode for a proton-conducting ceramic cell and a proton-conducting ceramic cell using the same. The air electrode of the above proton-conducting ceramic cell consists of a perovskite-type electronically conductive oxide material for air electrodes and a perovskite-type proton-conducting oxide material. The electrolyte also consists of a perovskite-type proton-conducting oxide material. It is suggested that this proton-conducting ceramic cell achieves both high durability and high power density.
[0006] Furthermore, Japanese Patent Publication No. 2024-090108 discloses an electrode for a proton-conducting ceramic cell, a proton-conducting ceramic cell using the same, and a method for manufacturing the same. The electrode for the proton-conducting ceramic cell is formed of an electronically conductive material and a proton-conducting material. The mass ratio of the electronically conductive material and the proton-conducting material is 90:10 to 10:90. The porosity of the electrode is 32.0 to 45.0 volume%. In addition, in the pore distribution of the electrode measured by the mercury intrusion method, at least a first and second peak top are observed in the pore diameter range of 0.10 to 2.0 μm, and the pore diameter at which the cumulative pore volume is 50% (median pore diameter) is 0.20 to 1.0 μm. It is suggested that the reaction field within the electrode is expanded, the electrode resistance is reduced, and the current density is increased because the mass ratio, porosity, and pore diameter are within the above ranges. [Prior art documents] [Patent Documents]
[0007] [Patent Document 1] Japanese Patent Publication No. 2023-006322 [Patent Document 2] Japanese Patent Publication No. 2024-074357 [Patent Document 3] Japanese Patent Publication No. 2024-090108 [Overview of the project] [Problems that the invention aims to solve]
[0008] Incidentally, the inventor has been attempting to form an intermediate layer for a proton-conducting fuel cell using inkjet printing. The inventor has found that by controlling the structure (particle packing) of the intermediate layer to a thin film, the durability of the proton-conducting fuel cell can be improved. However, ink ejection is unstable in inkjet printing. As a result, the thickness of the intermediate layer is not uniform, and uneven printing sometimes occurs. After diligent research, the inventor has succeeded in forming an intermediate layer of uniform thickness. With an electrode containing this intermediate layer of uniform thickness, it is possible to stabilize the potential while improving the current-voltage characteristics. [Means for solving the problem]
[0009] Therefore, this disclosure aims to provide a method for manufacturing a proton-conducting ceramic fuel cell using inkjet printing. It also aims to provide an inkjet ink used in the method for manufacturing such a proton-conducting ceramic fuel cell. Furthermore, it aims to provide electrodes for a proton-conducting ceramic fuel cell manufactured using such an inkjet ink. In the technology disclosed herein, each component and each process mentioned herein may be omitted or combined as appropriate, unless no particular problems arise.
[0010] [Section 1] An electrode for a proton-conducting ceramic fuel cell, comprising: an air electrode containing cobalt (Co); a proton-conducting solid electrolyte membrane containing zirconium (Zr) and / or cerium (Ce) and barium (Ba); a fuel electrode; and an intermediate layer formed between the air electrode and the solid electrolyte membrane, wherein the intermediate layer contains a perovskite-type oxide containing at least cerium (Ce) and barium (Ba); the average film thickness of the intermediate layer when measured at 15 or more locations in the stacking direction of the air electrode and the solid electrolyte membrane is 0.5 μm or more and 5 μm or less; and the standard deviation of the average film thickness is 0.3 μm or less.
[0011] [Section 2] The perovskite-type oxide contained in the intermediate layer is represented by the following formula (3): (Ba α3 A3 1-α3 ) x3 (Ce β3 B3 1-β3 ) y3 O 3+δ3 (3) (wherein A3 is at least one selected from the group consisting of calcium (Ca), strontium (Sr), and lanthanum (La), B3 is at least one selected from the group consisting of zirconium (Zr), yttrium (Y), and ytterbium (Yb), α3 is 0.2 to 1, x3 is 0.8 to 1.2, β3 is 0.1 to 1.0, y3 is 0.8 to 1.2, and δ3 is -0.8 to 0.8.) The electrode according to [Claim 1], which satisfies
[0012] [Claim 3] The solid electrolyte membrane is represented by the following formula (4): (Ba α4 A4 1-α4 ) x4 (B4 β4 C4 1-β4 ) y4 O 3+δ4 (4) (wherein A4 is at least one selected from the group consisting of calcium (Ca), strontium (Sr), and lanthanum (La), B4 is at least one selected from the group consisting of zirconium (Zr) and cerium (Ce), C4 is at least one selected from the group consisting of yttrium (Y) and ytterbium (Yb), α4 is 0.2 to 1, x4 is 0.8 to 1.2, β4 is 0.1 to 1.0, y4 is 0.8 to 1.2, and δ4 is -0.8 to 0.8.) The electrode according to [Claim 1] or [Claim 2], comprising a proton-conductive oxide that satisfies
[0013] [Claim 4] The electrode for a proton-conductive ceramic fuel cell according to any one of [Claim 1] to [Claim 3], wherein the intermediate layer is a porous body.
[0014] [Section 5] An inkjet printing ink used in the manufacture of electrodes for proton-conducting ceramic fuel cells, comprising a perovskite-type oxide powder containing at least cerium (Ce) and barium (Ba), and a dispersion medium, wherein the perovskite-type oxide powder has an average particle size of 50 nm to 1000 nm based on laser diffraction / light scattering, and the surface tension of the dispersion medium is 29 mN / m or less.
[0015] [Section 6] The ink according to item 5, wherein when the total mass of the perovskite-type oxide powder and the dispersion medium in the ink is 100 mass%, the content of the perovskite-type oxide powder is 5 mass% or more and 30 mass% or less, and the content of the dispersion medium is 70 mass% or more and 95 mass% or less.
[0016] [Section 7] The ink according to item 6, wherein the dispersion medium comprises at least one selected from hexanol and diethylene glycol dibutyl ether.
[0017] [Section 8] The process includes the steps of: preparing an ink by mixing a perovskite-type oxide powder containing at least cerium (Ce) and barium (Ba) with a dispersion medium; inkjet printing the ink onto the surface of a proton-conducting solid electrolyte membrane containing zirconium (Zr) and / or cerium (Ce) and barium (Ba); and forming an intermediate layer on the surface of the solid electrolyte membrane by sintering the ink, wherein when 20 μL of the ink is dropped onto a substrate, the contact angle θ is given by the following equation (5): θ = 2tan -1 (h / r) (5) (Here, r is the radius of the surface of the water droplet in contact with the substrate, and h is the height from the substrate to the top of the water droplet.) A method for manufacturing electrodes for a proton-conducting ceramic fuel cell, satisfying the condition of 25° or less.
[0018] [Section 9] The method for producing an electrode according to item 8, wherein the dispersion medium comprises at least one selected from hexanol and diethylene glycol dibutyl ether.
[0019] This disclosure provides an electrode for a proton-conducting ceramic fuel cell having an intermediate layer with uniform thickness. The electrode for the proton-conducting ceramic fuel cell exhibits excellent power generation characteristics (e.g., initial IV characteristics). In addition, the electrode for the proton-conducting ceramic fuel cell maintains a stable potential during continuous operation. [Brief explanation of the drawing]
[0020] [Figure 1] This is a schematic cross-sectional view showing the configuration of the electrodes of the proton-conducting ceramic fuel cell disclosed herein. [Figure 2] This is an optical photograph of the ink used in the comparative example when inkjet printing was performed on a nonwoven fabric. [Figure 3] This is an optical photograph of the ink used in the example when inkjet printing was performed on a nonwoven fabric. [Figure 4] This is an optical photograph of the ink used in the comparative example when it was dropped onto the substrate glass surface for wettability evaluation. [Figure 5] This is an optical photograph taken when the ink described in the example was dropped onto the substrate glass surface for wettability evaluation. [Figure 6A] This is a cross-sectional SEM image 1 of the intermediate layer in the comparative example. [Figure 6B] This is a cross-sectional SEM image 2 of the intermediate layer in the comparative example. [Figure 6C] This is a cross-sectional SEM image 3 of the intermediate layer in the comparative example. [Figure 7A] This is a cross-sectional SEM image 1 of the intermediate layer in the example. [Figure 7B] This is a cross-sectional SEM image 2 of the intermediate layer in the example. [Figure 7C] This is a cross-sectional SEM image 3 of the intermediate layer in the example. [Figure 8] This is a graph of the current-voltage characteristics and power density in the comparative example. [Figure 9] This is a graph showing the current-voltage characteristics and power density in the example. [Figure 10] This is a graph showing the potential variation of the comparative example in the continuous operation evaluation. [Figure 11] This is a graph showing the potential variation in the examples during continuous operation evaluation. [Modes for carrying out the invention]
[0021] Typical embodiments of this disclosure will be described in detail below. Matters other than those specifically mentioned herein but necessary for implementation can be understood as design matters for those skilled in the art based on the prior art. This disclosure can be implemented based on the contents disclosed herein and common technical knowledge in the art. In the drawings described herein, the same reference numerals are used to denote members and parts that perform the same function, and redundant explanations may be omitted or simplified. Also, the dimensional relationships (length, width, thickness, etc.) in each drawing do not necessarily reflect the actual dimensional relationships.
[0022] In this specification, when a numerical range is described as "A to B (where A and B are arbitrary numbers)," it means "greater than or equal to A and less than or equal to B," and also encompasses the meanings of "greater than A and less than B," "greater than A and less than or equal to B," and "greater than or equal to A and less than B."
[0023] <Proton-conducting ceramic fuel cell> Figure 1 is a schematic cross-sectional view showing an example of the configuration of electrode 1 of the proton-conducting ceramic fuel cell disclosed herein. In Figure 1, arrows indicate the flow of ions, etc., to show the mechanism of power generation of the proton-conducting ceramic fuel cell at the cell level. As shown in Figure 1, the proton-conducting ceramic fuel cell (hereinafter also simply referred to as "PCFC") uses hydrogen ions (H) in the solid electrolyte. + This fuel cell uses oxide ions (O) as charge carriers for convenience in this specification. 2- Compared to solid oxide fuel cells (SOFCs) that use ) as a charge carrier, PCFCs can operate at low temperatures and have high fuel efficiency.
[0024] As shown in Figure 1, the electrode 1 of the PCFC disclosed herein includes a fuel electrode 30, an air electrode 40, a solid electrolyte membrane 50, and an intermediate layer 100. The solid electrolyte membrane 50 is interposed between the fuel electrode 30 and the air electrode 40, insulating them from each other.
[0025] Furthermore, although not shown in detail, the electrode 1 of the PCFC according to this embodiment may have a fuel electrode-side gas channel outside the fuel electrode 30 for supplying gas (e.g., air, natural gas, etc.) to the fuel electrode 30, and a fuel electrode-side gas diffusion layer. Also, the electrode 1 of the PCFC according to this embodiment may have an air electrode-side gas channel outside the air electrode 40 for supplying hydrogen (H2) gas to the air electrode 40, and an air electrode-side gas diffusion layer. The fuel electrode-side gas diffusion layer and the air electrode-side gas diffusion layer promote the diffusion of the gas supplied from the gas channel, allowing for more efficient chemical reactions within the electrodes. However, the fuel electrode-side gas diffusion layer and the air electrode-side gas diffusion layer are not essential and can be omitted in other examples. Furthermore, although not shown in detail, the fuel electrode 30 and the air electrode 40 may be electrically connected to an external circuit 200.
[0026] In this embodiment, the fuel electrode 30 may be an anode electrode. The air electrode 40 may be a cathode electrode. Therefore, the electrode reaction described in formula (1) below may occur at the fuel electrode 30. The electrode reaction described in formula (2) below may occur at the air electrode 40. H2→2H+ +2e - (1) 1 / 2O2+2H + +2e - →H2O (2)
[0027] In the electrode 1 of the PCFC according to this embodiment, hydrogen (H2) gas is supplied to the fuel electrode 30 as a reducing gas. Then, in the fuel electrode 30, the hydrogen gas is oxidized by the action of a catalyst, and hydrogen ions (H2) are formed. + ) and electrons (e - ) is generated. Hydrogen ions move to the air electrode 40 by permeating through the intermediate layer 100 and the proton-conducting solid electrolyte membrane 50. Oxygen (O2) gas is supplied to the air electrode 40. At the air electrode 40, the moved hydrogen ions react with oxygen to produce water (H2O). In addition, the generated electrons move from the fuel electrode 30 to the air electrode 40 via the external circuit 200.
[0028] <Middle class> Next, the configuration of each layer of the PCFC electrode 1 disclosed herein will be described in detail. The PCFC electrode 1 disclosed herein comprises an air electrode 40 containing cobalt (Co), a proton-conducting solid electrolyte membrane 50 containing zirconium (Zr) and / or cerium (Ce) and barium (Ba), and a fuel electrode 30. In addition, the PCFC electrode 1 disclosed herein comprises an intermediate layer 100 formed between the air electrode 40 and the solid electrolyte membrane 50. The intermediate layer 100 is a sheet-like member provided between the fuel electrode 30 or the air electrode 40 and the solid electrolyte membrane 50. The intermediate layer 100 is provided for various purposes. Typically, the intermediate layer 100 may be provided for purposes such as preventing gas leaks, suppressing electron leaks, reducing the reaction resistance of the fuel electrode 30 and the air electrode 40, and improving the adhesion strength of the interface between the fuel electrode 30 or the air electrode 40 and the solid electrolyte membrane 50. As shown in Figure 1, in the PCFC1 according to this embodiment, the intermediate layer 100 is interposed between the solid electrolyte membrane 50 and the air electrode 40. The intermediate layer 100 has the function of allowing protons to pass through. Therefore, protons that have moved from the fuel electrode 30 through the solid electrolyte membrane 50 can move to the air electrode 40. In some embodiments, the intermediate layer may also be provided between the fuel electrode and the solid electrolyte membrane.
[0029] The intermediate layer 100 of the electrode 1 of the PCFC disclosed herein comprises a perovskite-type oxide containing at least cerium (Ce) and barium (Ba). Perovskite-type proton-conducting oxides are preferably used in the intermediate layer 100 because of their high proton conductivity. Such perovskite-type oxides, due to the presence of cerium, allow metal ions (e.g., cobalt ions (Co)) contained in the fuel electrode 30 and air electrode 40 to be absorbed. 2+ This tends to reduce the effects of (etc.). As a result, the degradation of the solid electrolyte membrane 50 can be suppressed. Furthermore, the proton conductivity of such perovskite-type oxides is improved due to the inclusion of barium. As a result, the permeability of protons from the air electrode 40 to the solid electrolyte membrane 50 is easily improved.
[0030] Furthermore, in a preferred embodiment of the electrode 1 of the PCFC disclosed herein, the intermediate layer 100 is given by the following formula (3): (Ba α3 A3 1-α3 ) x3 (Ce β3 B3 1-β3 ) y3 O 3+δ3 (3) (Here, A3 is at least one selected from calcium (Ca), strontium (Sr), and lanthanum (La); B3 is at least one selected from zirconium (Zr), yttrium (Y), and ytterbium (Yb); α3 is 0.2 to 1; x3 is 0.8 to 1.2; β3 is 0.1 to 1.0 (more preferably 0.2 to 0.9); y3 is 0.8 to 1.2 (more preferably 0.9 to 1.1); and δ3 is -0.8 to 0.8.) It contains a pevrosite-type oxide that satisfies the following condition. Note that (Ba in formula (2) above) α3 A2 1-α3 ) x3 This indicates the A site in the perovskite structure. Also, (Ce in equation (2) above) β3 B2 1-β3 ) y3 This indicates the B site in the perovskite structure.
[0031] Examples of perovskite-type oxides shown in formula (3) above include BaZr 0.4 Ce 0.4 Y 0.1 O3, BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 Examples include O3. The perovskite-type oxide contained in the intermediate layer 100 of the electrode 1 of the PCFC disclosed herein may be one type or two or more types.
[0032] In the above formula (3), the inclusion of zirconium at site B is preferable because it improves CO2 resistance. The inclusion of cerium at site B is presumed to suppress the degradation of the solid electrolyte membrane 50. Furthermore, the inclusion of yttrium and ytterbium at site B is preferable because it makes it less likely to form a composite oxide with nickel oxide, which can reduce proton conductivity.
[0033] Furthermore, the intermediate layer 100 of the electrode 1 of the PCFC disclosed herein may contain other components (e.g., electronically conductive materials) in addition to the perovskite-type oxide described above. Examples include LaCoO3 and BaCoO3.
[0034] Furthermore, the thickness (average film thickness) of the intermediate layer 100 of the electrode 1 of the PCFC disclosed herein is 0.5 μm or more and 5 μm or less. If the average film thickness of the intermediate layer 100 is within the above range, metal ions (e.g., cobalt ions (Co)) that have desorbed from the electronically conductive material contained in the air electrode 40 will not be absorbed. 2+This can suppress the diffusion of ions (such as ions) into the solid electrolyte membrane 50. It can also improve the adhesion strength between the fuel electrode 30 or air electrode 40 and the solid electrolyte membrane 50, thereby improving the durability of the electrode 1 of the PCFC. However, if the average thickness of the intermediate layer 100 is too large, the proton permeability may decrease. Also, if the average thickness of the intermediate layer 100 is larger, the energy density of the PCFC tends to decrease. From this viewpoint, the upper limit of the average thickness of the intermediate layer is preferably 5 μm or less, more preferably 4 μm or less, and even more preferably 3 μm or less. However, if the average thickness of the intermediate layer 100 is larger, it becomes easier to suppress the diffusion of metal ions from the fuel electrode 30 and air electrode 40 into the solid electrolyte membrane 50. From this viewpoint, the lower limit of the average thickness of the intermediate layer is preferably 0.5 μm or more, more preferably 1 μm or more, and even more preferably 2 μm or more. When the average film thickness of the intermediate layer 100 is denoted as Dm, as shown in Figure 1, Dm represents the length of the intermediate layer 100 in the stacking direction Z of the air electrode 40 and the solid electrolyte membrane 50. The average film thickness can be measured, for example, by a scanning electron microscope (SEM). In this specification, the average film thickness Dm of the intermediate layer 100 is the average value obtained when the film thickness dm of the intermediate layer 100 observed in cross-sectional SEM images along the stacking direction Z of the air electrode 40 and the solid electrolyte membrane 50 is measured at 15 or more random locations (see Figures 7A to 7C). Although it cannot be defined in general terms as it depends on the cross-section measured, in some embodiments, from the viewpoint of improving measurement accuracy and reproducibility, a cross-section of the electrode 1 of the PCFC is photographed with an SEM in a field of view within a range of approximately 1000x to 3000x, and the film thickness dm is measured at 5 random locations within the intermediate layer 100 that exist in that field of view. This is done with at least 3 images, and the average film thickness Dm is calculated from a total of 15 or more film thickness dm.
[0035] In addition, the standard deviation u of the average film thickness Dm of the intermediate layer 100 of the electrode 1 of the PCFC disclosed herein is 0.3 μm or less. Such an intermediate layer 100 has little variation in thickness. This improves the initial IV characteristics by improving adhesion with the air electrode 40 and suppressing the diffusion of metal ions into the solid electrolyte membrane 50. In addition, it allows for voltage stabilization during continuous operation. From the viewpoint of more favorably exhibiting the effects of the technology disclosed herein, the standard deviation u is preferably 0.25 μm or less, more preferably 0.2 μm or less, and even more preferably 0.15 μm or less. The above average film thickness and its standard deviation can be achieved by the ink or the method for manufacturing the electrode 1 of the PCFC disclosed herein, which will be described later.
[0036] By the way, in PCFCs, if power generation continues (due to the effects of high temperature environment and the presence of oxygen gas), metal ions contained in the air electrode (for example, cobalt ions (Co)) 2+ Metal ions may detach from the electron-conducting material and diffuse into the solid electrolyte membrane. This can reduce the proton conductivity of the solid electrolyte membrane, potentially degrading power generation characteristics. Furthermore, if the detachment of metal ions increases significantly, it can alter the structure of the electron-conducting material, potentially causing the air electrode to detach from the solid electrolyte membrane. The inventor attempted to suppress the diffusion of metal ions into the solid electrolyte membrane by providing an intermediate layer between the air electrode and the solid electrolyte membrane.
[0037] Therefore, the inventor improved the power generation characteristics and durability by controlling the structure of the intermediate layer (e.g., thinning and porosity) by inkjet printing the ink used to form the intermediate layer onto the substrate. Furthermore, the inventor made the intermediate layer thin (specifically, the average film thickness Dm of the intermediate layer is 0.5 μm or more and 5 μm or less). This improved the output characteristics of the PCFC.
[0038] However, with inkjet printing, it is difficult to stabilize ink ejection, which can result in uneven thickness of the printed intermediate layer. Through diligent research by the inventors, it was discovered that by using an ink prepared to have a wettability within a predetermined range (contact angle θ ≤ 25°) as the raw material for the intermediate layer, uniform ink ejection onto the substrate was achieved. When such ink is ejected onto the substrate by inkjet printing, its affinity with the substrate is improved. As a result, an intermediate layer of uniform thickness (u ≤ 0.3 μm) can be formed. This improves the adhesion between the intermediate layer and the air electrode. Furthermore, the diffusion of metal ions into the solid electrolyte membrane 50 can be suppressed more reliably. As a result, the initial IV characteristics can be improved. In addition, variations in potential during continuous operation can be suppressed.
[0039] Furthermore, in some embodiments, the coefficient of variation of the average film thickness Dm is 50% or less. Moreover, from the viewpoint of more favorably exhibiting the effects of the technology of this disclosure, the coefficient of variation is preferably 30% or less, more preferably 25% or less, and even more preferably 15% or less. The coefficient of variation can be calculated as a percentage of the value obtained by dividing the standard deviation by the arithmetic mean (standard deviation / arithmetic mean).
[0040] In a preferred embodiment of the intermediate layer of the PCFC disclosed herein, the intermediate layer may be a porous material. This increases the contact area with the electrode and the solid electrolyte membrane, thereby reducing interfacial resistance. It also improves adhesion to the electrode and suppresses electrode delamination. The lower limit of the porosity of the intermediate layer as a porous material is preferably 10% or more, more preferably 20% or more, and even more preferably 30% or more. On the other hand, if the porosity is too high, the mechanical strength of the PCFC may decrease. Also, proton movement may be restricted. From this viewpoint, the upper limit of the porosity of the intermediate layer is preferably 90% or less, more preferably 80% or less, and even more preferably 70% or less. The porosity can be calculated, for example, by performing binarization processing in cross-sectional observation by SEM.
[0041] <Solid electrolyte membrane> The electrode 1 of the PCFC disclosed herein comprises a solid electrolyte membrane 50. The solid electrolyte membrane 50 is a sheet-like member that insulates the fuel electrode 30 and the air electrode 40. The solid electrolyte membrane 50 also typically acts as a gas separator that blocks gas between the fuel electrode 30 and the air electrode 40. Therefore, the solid electrolyte membrane 50 can be a dense material. The porosity of the solid electrolyte membrane 50 can be, for example, 0% to 10% (preferably 0% to 2%). Having the porosity of the solid electrolyte membrane 50 within the above range makes it easier to prevent gas leaks.
[0042] The solid electrolyte membrane 50 of the electrode 1 of the PCFC disclosed herein is formed using a proton-conducting (proton-permeable) ceramic material. Therefore, protons that have moved from the fuel electrode 30 through the solid electrolyte membrane 50 can move to the air electrode 40.
[0043] Furthermore, the solid electrolyte membrane 50 disclosed herein includes zirconium and / or cerium and barium. The solid electrolyte membrane 50 improves proton conductivity by including barium. This promotes chemical reactions within electrode 1, potentially improving the energy efficiency of the PCFC. The solid electrolyte membrane 50 can improve CO2 resistance by including zirconium. Therefore, natural gas can be suitably used as fuel. In addition, the solid electrolyte membrane 50 can improve CO2 resistance by including cerium, thereby reducing metal ions (e.g., cobalt ions (Co)) contained in the fuel electrode 30 and air electrode 40. 2+ The effects of (etc.) can be suppressed.
[0044] Furthermore, in a preferred embodiment of the electrode 1 of the PCFC disclosed herein, the solid electrolyte membrane 50 is given by the following formula (4): (Ba α4 A1 1-α4 ) x4 (B4 β4 C4 1-β4 ) y4 O 3+δ4 (4) (Here, A4 is at least one selected from calcium (Ca), strontium (Sr), and lanthanum (La); B4 is at least one selected from zirconium (Zr) and cerium (Ce); C4 is at least one selected from yttrium (Y) and ytterbium (Yb); α4 is 0.2 to 1; x4 is 0.8 to 1.2; β4 is 0.1 to 1.0; y4 is 0.8 to 1.2 (more preferably 0.9 to 1.1); and δ4 is -0.8 to 0.8.) It includes an electronically conductive material that satisfies the above formula (4). The electronically conductive material of formula (4) above may be a perovskite-type oxide. Such a perovskite-type oxide (Ba α4 A4 1-α4 ) x4 This indicates the A site in the perovskite structure. Also, (B4) of such perovskite-type oxides β4 C4 1-β4 ) y4 This indicates the B site in the perovskite structure.
[0045] Examples of the electronically conductive material shown in formula (4) above include BaZrYbO3 and BaCeYbO3. The electronically conductive material contained in the solid electrolyte membrane 50 of the electrode 1 of the PCFC disclosed herein may be one type or two or more types. Furthermore, the solid electrolyte membrane 50 of the electrode 1 of the PCFC disclosed herein may contain any components other than the electronically conductive material described above.
[0046] In formula (4) above, increasing the cerium content tends to improve the ability to suppress cobalt ion diffusion. However, increasing the cerium content tends to decrease CO2 resistance. For this reason, it is preferable that zirconium is included in the B site in formula (1). Zirconium can improve the CO2 resistance of the solid electrolyte membrane 50. From this viewpoint, β4 is preferably 0.2 to 0.9, more preferably 0.3 to 0.8. This makes it possible to suppress cobalt ion diffusion while maintaining CO2 resistance. As a result, the degradation of the electrode 1 of the PCFC can be suppressed. In addition, ytterbium or yttrium may be included in the B site of formula (1) above. This makes it less susceptible to the effects of diffusion of cobalt ions, etc.
[0047] The thickness (average film thickness) De of the solid electrolyte membrane 50 is not particularly limited. The smaller the average film thickness of the solid electrolyte membrane 50, the smaller the proton migration distance, which tends to reduce the internal resistance of the PCFC electrode 1 and improve the output. Therefore, the upper limit of the average film thickness De is preferably 15 μm or less, more preferably 10 μm or less, and even more preferably 8 μm or less. On the other hand, the larger the average film thickness of the solid electrolyte membrane 50, the better the mechanical strength of the PCFC electrode 1 and the less likely gas leaks are to occur. Therefore, the lower limit of the average film thickness De is preferably 3 μm or more, more preferably 5 μm or more, and even more preferably 6 μm or more.
[0048] <Air pole> The electrode 1 of the PCFC disclosed herein includes an air electrode 40. As shown in Figure 1, the air electrode 40 is a layered member provided on an intermediate layer 100.
[0049] The air electrode 40 disclosed herein contains cobalt (Co). The presence of cobalt significantly improves the proton conductivity of the air electrode 40. This promotes chemical reactions within the electrode 1 of the PCFC, potentially improving the energy efficiency of the PCFC.
[0050] Furthermore, in one preferred embodiment of the PCFC electrode 1 disclosed herein, the air electrode 40 is given by the following formula (5): (A5 α5 B5 1-α5 ) x5 (Co β5 C5 1-β5 ) y5 O 3-δ5 (5) (Here, A5 is at least one selected from strontium (Sr), calcium (Ca), and barium (Ba); B5 is at least one selected from yttrium (Y), lanthanum (La), cerium (Ce), praseodymium (Pr), samarium (Sm), and gadolinium (Gd); C5 is at least one selected from chromium (Cr), manganese (Mn), iron (Fe), nickel (Ni), and copper (Cu); α5 is 0.2 to 0.6; x5 is 0.8 to 1.2; β5 is 0.1 to 1; y5 is 0.8 to 1.2; and δ5 is -1 to 1.) It includes an electronically conductive material that satisfies the above formula (5). The electronically conductive material of formula (5) may be a perovskite-type oxide. Such a perovskite-type oxide (A5 α5 B5 1-α5 ) x5 This indicates the A site in the perovskite structure. Furthermore, the (Co) of such perovskite-type oxides β5 C5 1-β5 ) y5 This indicates the B site in the perovskite structure.
[0051] Examples of the electronically conductive materials shown in formula (5) above include LaSrCoO3, LaSrCoFeO3, and LaBaCoO3. The electronically conductive material contained in the air electrode 40 of the electrode 1 of the PCFC disclosed herein may be one type or two or more types. Furthermore, the air electrode 40 of the electrode 1 of the PCFC disclosed herein may contain any components other than the electronically conductive materials described above.
[0052] In the above formula (5), the B site contains cobalt as a catalyst for the electrochemical reaction (typically in an elemental ratio of 10% or more in the B site). The B site may also contain other elements besides cobalt. For example, it is preferable that the B site contains strontium and / or iron. The presence of strontium causes oxygen deficiency, improving the conductivity of oxide ions. The presence of iron tends to lower the coefficient of thermal expansion. This can improve the adhesion between the solid electrolyte membrane 50 and the intermediate layer 100. From this viewpoint, β5 is preferably 0.2 to 0.9, and more preferably 0.3 to 0.8. Also, y5 may be 0.9 to 1.1.
[0053] The thickness (average film thickness) Dc of the air electrode is not particularly limited. The smaller the average film thickness of the air electrode, the smaller the gas diffusion resistance, which is part of the electrode resistance. Therefore, the current density of the PCFC can be improved. From this viewpoint, the upper limit of the average film thickness Dc is preferably 100 μm or less, more preferably 50 μm or less, and even more preferably 30 μm or less. On the other hand, the larger the average film thickness of the air electrode, the more electron-conducting material there is, and the more likely the efficiency of the electrode reaction is to improve. Therefore, the lower limit of the average film thickness Dc is preferably 3 μm or more, more preferably 5 μm or more, and even more preferably 10 μm or more.
[0054] The porosity of the air electrode 40 is not particularly limited. However, in some embodiments, the air electrode may be a porous body. A higher porosity of the air electrode tends to increase the contact area between the air electrode and the intermediate layer, and decrease the interfacial resistance. It also tends to reduce the gas diffusion resistance. Therefore, the lower limit of the porosity of the air electrode is preferably 10% or more, more preferably 20% or more, and even more preferably 30% or more. A lower porosity of the air electrode tends to improve the efficiency of the electrode reaction. Therefore, the upper limit of the porosity of the air electrode is preferably 70% or less, more preferably 60% or less, and even more preferably 50% or less.
[0055] <Fuel electrode> The electrode 1 of the PCFC disclosed herein comprises a fuel electrode 30. As shown in Figure 1, the fuel electrode 30 is a layered member provided opposite the air electrode 40. In this embodiment, the fuel electrode 30, solid electrolyte membrane 50, intermediate layer 100, and air electrode 40 are stacked in this order. The fuel electrode 30 can be made of any known material (e.g., electronically conductive material, catalyst, etc.) that can be used in this type of fuel cell (not limited to PCFCs, but including, for example, SOFCs). Examples of electronically conductive materials included in the fuel electrode 30 include zirconium oxide (ZrO2), yttrium oxide (Y2O3), cerium oxide (CeO2), and oxides thereof doped with yttrium, ytterbium (Yb), or calcium (Ca), etc. More specifically, such an electronically conductive material is, for example, BaZrYbO3. The fuel electrode 30 may also contain any component such as nickel oxide (NiO).
[0056] <Ink used to form the intermediate layer> Next, the composition of the ink for forming the intermediate layer described above will be explained. The ink described here can typically be used as an inkjet ink as a raw material for the intermediate layer 100. The ink disclosed herein comprises a perovskite-type oxide powder containing at least cerium (Ce) and barium (Ba), and a dispersion medium. When such an ink is applied to a substrate (here, a solid electrolyte film 50), it spreads uniformly and has little variation in droplet height. Therefore, an intermediate layer 100 of uniform thickness can be formed after sintering.
[0057] The ink disclosed herein includes a perovskite oxide (i.e., a perovskite oxide containing at least cerium and barium) contained in the intermediate layer 100 described above. The ink disclosed herein also includes a dispersion medium for dispersing the perovskite oxide powder, etc. The ink disclosed herein may also contain any components other than the perovskite oxide powder and the dispersion medium, as long as they do not significantly impair the effects of the technology of this disclosure. In some embodiments, the ink according to this disclosure may include, for example, a resin, a dispersant, etc. The resin may typically be added as a binder to bind the perovskite oxide powders together and improve the formation of the intermediate layer. The dispersant may typically be added to further improve the dispersion of the perovskite oxide powder. The resin and dispersant may be those conventionally used in this type of ink and are not particularly limited. Examples of resins include ethylcellulose, acrylic resin, butyral resin, etc. Examples of dispersants include polyethylene glycol, polyacrylic acid, and polyoxyethylene alkyl ether.
[0058] <Perovskite-type oxide powder> The perovskite oxide powder contained in the ink disclosed herein may be formed from the perovskite oxide contained in the intermediate layer 100 described above. The average particle size of the perovskite oxide powder contained in the ink disclosed herein is 50 nm or more and 1000 nm or less. If the average particle size is within the above range, the viscosity of the ink will not become too high. Therefore, ink ejection by inkjet printing can be stabilized. Also, as the average particle size increases, the perovskite oxide powder tends to become more stable. From this viewpoint, the lower limit of the average particle size is preferably 0.01 μm or more, more preferably 0.05 μm or more, and even more preferably 0.1 μm or more. If the average particle size decreases, ink ejection improves further. As a result, it becomes easier to uniformly coat the surface of the substrate with ink. From this viewpoint, the upper limit of the average particle size is preferably 1 μm or less, more preferably 0.5 μm or less, and even more preferably 0.3 μm or less. In this specification, "average particle size" refers to the particle size (D50 particle size) corresponding to the cumulative 50% from the finest particles in the volume-based particle size distribution measured by laser diffraction / light scattering. Furthermore, the shape of the perovskite oxide powder is not particularly limited. The shape of the perovskite oxide powder can typically be approximately spherical. In this specification, the term "approximately spherical" refers to a shape that can be considered roughly spherical overall, with an average aspect ratio (major axis / minor axis ratio) based on electron microscope observation images being approximately 1 to 2, for example, 1 to 1.5.
[0059] <Dispersion medium> The surface tension of the dispersion medium contained in the ink disclosed herein is 29 mN / m or less. If the surface tension is below the above value, the ink ejection by inkjet printing can be stabilized. Furthermore, from the viewpoint of improving the dispersion of perovskite-type oxide powder, the upper limit of the surface tension is preferably 28 mN / m or less, more preferably 27.5 mN / m or less, and even more preferably 27 mN / m or less. In this specification, the term "surface tension" for dispersants refers to the static surface tension measured, for example, by the Wilhelmy method at 20°C.
[0060] Examples of dispersion media that satisfy the above surface tension include hexanol and diethylene glycol dibutyl ether. In a preferred embodiment of the ink disclosed herein, the dispersion media is composed of at least one selected from hexanol and diethylene glycol dibutyl ether. Such dispersion media improve the discharge and wettability of the ink. Therefore, when the ink is applied to a substrate, a film with less unevenness can be formed. Note that only one type of dispersion media may be used alone. However, the dispersion media only needs to be within the above surface tension range, and a mixed solvent obtained by mixing two or more types of dispersion media may also be used.
[0061] The content of perovskite oxide powder in the ink disclosed herein is not particularly limited, as long as it does not significantly impair the effects of the technology described herein. However, the viscosity of the ink tends to increase as the proportion of perovskite oxide powder in the ink increases. From this viewpoint, when the total mass in the ink disclosed herein is 100 mass%, the content of perovskite oxide powder may typically be between 5 mass% and 70 mass%. Furthermore, the ink's discharge performance tends to improve as the content of perovskite oxide powder decreases. Therefore, the upper limit of the perovskite oxide powder content may be 65 mass% or less, preferably 50 mass% or less, more preferably 40 mass% or less, and even more preferably 30 mass% or less. The lower limit of the perovskite oxide powder content may be 6 mass% or more, preferably 7 mass% or more, and may be 7.5 mass% or more.
[0062] The content of the dispersion medium in the ink disclosed herein is not particularly limited, as long as it does not significantly impair the effects of the technology relating to this disclosure. When the total mass in the ink disclosed herein is 100 mass%, the content of the perovskite-type oxide powder is typically 25 mass% to 95 mass%. As the proportion of the dispersion medium in the ink increases, the ink's discharge performance tends to improve. From this viewpoint, the lower limit of the dispersion medium content is preferably 30 mass% or more, more preferably 35 mass% or more, even more preferably 40 mass% or more, and may be 50 mass% or more. The upper limit of the dispersion medium content may be 94.5 mass% or less, 94 mass% or less, or 92 mass% or less.
[0063] In one preferred embodiment of the ink disclosed herein, the ink may further contain a resin. The resin content is not particularly limited, as long as it does not significantly impair the effects of the technology disclosed herein. When the total mass of the ink disclosed herein is 100 mass%, the resin content is 0 mass% or more and 5 mass% or less (preferably 0.3 mass% or more and 5 mass% or less). From the viewpoint of improving ink discharge performance, the upper limit of the resin content is preferably 4.5 mass% or less, more preferably 4 mass% or less, and even more preferably 3 mass% or less. From the viewpoint of improving the formation of an intermediate layer, the lower limit of the resin content is preferably 0.4 mass% or more, more preferably 0.5 mass% or more, and may be 1 mass% or more.
[0064] In one preferred embodiment of the ink disclosed herein, the ink may further contain a dispersant. The dispersant content is not particularly limited, as long as it does not significantly impair the effects of the technology disclosed herein. When the total mass of the ink disclosed herein is 100 mass%, the dispersant content is 0 mass% or more and 20 mass% or less (preferably 0.5 mass% or more and 20 mass% or less). From the viewpoint of improving the dispersibility of the perovskite-type oxide powder, the lower limit of the dispersant content is preferably 0.6 mass% or more, may be 1 mass% or more, or 5 mass% or more. The upper limit of the dispersant content may be 17 mass% or less, may be 15 mass% or less, or may be 10 mass% or less.
[0065] <Manufacturing method for proton-conducting ceramic fuel cells (PCFCs)> Next, the method for manufacturing the electrode 1 of the PCFC described above will be explained. The method for manufacturing the electrode 1 of the PCFC disclosed herein includes the steps of: preparing an ink by mixing a perovskite-type oxide powder containing at least cerium (Ce) and barium (Ba) with a dispersant (step S01); inkjet printing the above ink onto the surface of a proton-conducting solid electrolyte membrane 50 containing zirconium (Zr) and / or cerium (Ce) and barium (Ba) (step S02); and forming an intermediate layer 100 on the surface of the solid electrolyte membrane 50 by sintering the above ink (step S03). It is preferable that steps S01 to S03 be performed in the order described above. However, the following explanation is not intended to limit the method for manufacturing the electrode 1 of the PCFC disclosed herein to the following order. For example, steps S01 to S03 may include other steps in any of the steps.
[0066] <Step S01> Step S01 is a step of preparing an ink by mixing a perovskite-type oxide powder containing at least cerium (Ce) and barium (Ba) with a dispersant. The ink prepared in step S01 can typically be used as an inkjet ink to form the intermediate layer 100. In other words, step S01 is a step of preparing an inkjet ink that will be the raw material for the intermediate layer 100.
[0067] Here, the ink described above is prepared. First, the perovskite oxide powder is dispersed in a dispersion medium. The dispersion method is not particularly limited, and conventionally known methods can be used without restriction. For example, the perovskite oxide powder and the dispersion medium can be mixed using a stirring and mixing device such as a ball mill, mixer, disperser, or kneader. If necessary, other components such as resins and dispersants can be mixed into the ink.
[0068] <Ink surface tension> Furthermore, when 20 μL of the ink disclosed herein is dropped onto a substrate (in this case, a solid electrolyte membrane 50), the contact angle θ is given by the following equation (5): θ = 2tan⁻¹(h / r) (5) The condition of 25° or less is satisfied. In formula (5) above, r represents the radius of the surface of the water droplet in contact with the substrate. In formula (5) above, h represents the height from the substrate to the top of the water droplet. Because the contact angle θ of the ink disclosed herein is within the above range, the ink spreads uniformly on the substrate when ejected by inkjet printing. From the viewpoint of suitably demonstrating this technology, the contact angle θ is preferably 40° or less, more preferably 30° or less, and even more preferably 25° or less. The above contact angle θ is measured by the static drop method, in reference to JIS R3257, in which an appropriate amount of liquid, 20 μL, is dropped onto the surface of the substrate glass.
[0069] <Step S02> Step S02 is a process of inkjet printing ink onto the surface of a proton-conducting solid electrolyte membrane 50 containing zirconium (Zr) and / or cerium (Ce) and barium (Ba). A preferred embodiment of such Step S02 may include a step of preparing the solid electrolyte membrane 50 (Step S02-1) and an inkjet printing step (Step S02-2).
[0070] First, an embodiment of step S02-1 will be described. As a method for manufacturing the solid electrolyte membrane 50, any method conventionally known for manufacturing this type of solid electrolyte membrane can be used without limitation. Here, as an example of a method for manufacturing the solid electrolyte membrane 50, a raw material slurry for a solid electrolyte membrane (including ink, paste, etc.) is prepared by mixing a proton-conducting ceramic material powder containing zirconium (Zr) and / or cerium (Ce) and barium (Ba), and a solvent for dispersing the ceramic material powder. A solid electrolyte membrane is formed by coating this raw material slurry onto any substrate and drying it. The method for coating the raw material slurry onto the substrate is not particularly limited. The coating method of the raw material slurry may be, for example, screen printing, gravure printing, inkjet printing, etc. After coating, the solid electrolyte membrane 50 can be obtained by sintering at approximately 1200°C to 1600°C for 1 to 10 hours.
[0071] Next, in the inkjet printing step (step S02-2), the ink prepared in step S01 is ejected onto the surface of the prepared solid electrolyte membrane 50 by inkjet printing. As described above, the inkjet ink disclosed herein is typically used on a substrate (here, the solid electrolyte membrane 50) to form the intermediate layer 100 of the electrode 1 of the PCFC. The ink disclosed herein has the surface tension described above. Therefore, even if the ink is ejected directly onto the sintered solid electrolyte membrane 50, a layer (film) with little variation in thickness can be formed. Directly ejecting the ink onto the surface of the solid electrolyte membrane 50 is preferable because it reduces the number of steps. However, the substrate is not limited to the solid electrolyte membrane 50. The ink disclosed herein may be directly attached to the surface of the solid electrolyte membrane, or it may be indirectly attached to the surface of the solid electrolyte membrane via, for example, transfer paper.
[0072] <Step S03> Step S03 involves sintering the ink ejected onto the surface of the solid electrolyte membrane 50. This step forms an intermediate layer 100 on the surface of the solid electrolyte membrane 50. The sintering conditions for step S03 are not particularly limited, as long as they do not significantly impair the effects of the present invention. For example, the solid electrolyte membrane 50 with the ink disclosed herein attached is fired at a maximum firing temperature set within the range of 450°C to 1600°C (preferably 800°C to 1400°C, more preferably 1000°C to 1350°C). The firing time can be within the range of 1 hour to 10 hours (preferably 2 hours to 8 hours).
[0073] <Formation of fuel electrode and air electrode> As a method for manufacturing the fuel electrode 30 and air electrode 40, any conventional manufacturing method known for this type of fuel cell can be used without limitation. Here, as an example, a raw material slurry is prepared by mixing the electronically conductive material powder for the fuel electrode 30 or air electrode 40 described above, and a solvent for dispersing the electronically conductive material powder. The fuel electrode 30 and air electrode 40 are formed by coating this raw material slurry onto any substrate and drying it. The method for coating the raw material slurry onto the substrate is not particularly limited. For example, the coating method for the raw material slurry may be screen printing, gravure printing, inkjet printing, etc. After coating, the fuel electrode 30 or air electrode 40 can be obtained by sintering at approximately 1200°C to 1600°C for 1 to 10 hours. [Examples]
[0074] The electrodes of the PCFC of this disclosure will be specifically described below with reference to examples and comparative examples. However, this disclosure is not intended to be limited to the examples described below.
[0075] <Fabrication of the fuel electrode> Nickel oxide (NiO), BaZrYbO3 (BZYb), and carbon were mixed in a mass ratio of 6:4:1. A toluene-based solvent (Fujifilm Wako Pure Chemical Industries, product code 204-01861), a binder, a plasticizer, and a dispersant were added, and the mixture was ball-milled for 48 hours to obtain a fuel electrode slurry. A fuel electrode green sheet was obtained by tape casting of the fuel electrode slurry. The fuel electrode green sheet was laminated to a thickness of approximately 0.7 μm, and the film thickness was adjusted by hot pressing.
[0076] <Fabrication of solid electrolyte membranes> In the fabrication of solid electrolyte membranes, BaZr 0.8 Yb 0.2A slurry for a solid electrolyte membrane was obtained by adding O3(BZYb), a toluene-based solvent, a binder, a plasticizer, and a dispersant, and ball-milling for 48 hours. This slurry for the solid electrolyte membrane was applied to the above-mentioned green sheet for the fuel electrode by spin-coating at 3000 rpm. Subsequently, an integral molded body of the solid electrolyte membrane and fuel electrode was obtained by co-sintering at 1475°C for 2 hours. The obtained solid electrolyte membrane was densified by co-sintering at high temperature.
[0077] <Intermediate layer preparation: Example> In the fabrication of the intermediate layer in the example, BaZr 0.4 Ce 0.4 Y 0.1 Yb 0.1 7.46 wt% of O3(BZCYYb) and 91.4803 wt% of hexanol (manufactured by Wako Pure Chemical Industries, Ltd., surface tension 27.0 mN / m) were mixed. To this mixture, 0.4597 wt% of ethylcellulose and 0.6 wt% of AD-508E (manufactured by NOF Corporation) were added. This mixture was dispersed in a ball mill for 2 hours to obtain the raw material ink for the intermediate layer. The surface tension of the ink at this time was measured according to the procedure described later. This raw material ink for the intermediate layer was applied to the solid electrolyte membrane by inkjet printing (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., DMP-2831). This was sintered at 1350°C for 5 hours to obtain an integral molded body of the fuel electrode, solid electrolyte membrane, and intermediate layer.
[0078] <Intermediate layer preparation: Comparative example> In the comparative example, 7.46 wt% of BZCYYb and 91.4803 wt% of butyl dicarbitol acetate (BDGA, NG-120, manufactured by Nippon Fragrance Co., Ltd., surface tension 27.0 mN / m) were mixed. To this mixture, 0.4597 wt% of ethyl cellulose and 0.6 wt% of KD-1 (manufactured by Croda) were added. This mixture was dispersed in a ball mill for 2 hours to obtain the raw material ink for the intermediate layer. The surface tension of the ink at this time was measured according to the procedure described later. This raw material ink for the intermediate layer was applied to the solid electrolyte membrane by inkjet printing. This was sintered at 1350°C for 5 hours to obtain an integral molded body consisting of the fuel electrode, solid electrolyte membrane, and intermediate layer.
[0079] <Fabrication of the air electrode> LaSrCoO3(LSC), terpineol, ethyl cellulose, a plasticizer, and a dispersant were mixed in a kneader and dispersed for 1 minute and 30 seconds to obtain an air electrode slurry. This air electrode slurry was coated onto the above intermediate layer to a thickness of 10 μm by screen printing (manufactured by Newlong Co., Ltd.). This was sintered at 1000°C for 1 hour to obtain the PCFC electrode according to the example and the PCFC electrode according to the comparative example.
[0080] <Measurement of ink wettability> For the raw material ink for the intermediate layer described above, the contact angle θ was measured when the droplet volume was 20 μL, referencing the drop method in the wettability test of the substrate glass surface specified in JIS R3257. The results of this wettability test are shown in Table 1. Figures 2 and 3 are optical photographs of the ink prepared above when dropped onto a nonwoven fabric. In the comparative example, unevenness can be observed on the surface. In contrast, a uniform film is formed in the example. Figures 4 and 5 are optical photographs of the ink prepared above when dropped onto the substrate glass surface in the wettability test.
[0081] [Table 1]
[0082] <Evaluation of power generation> For the electrodes of the PCFCs fabricated as described above, the current density, cell voltage, and power density were measured at cell temperatures of 500°C, 600°C, and 700°C, under conditions of 100% RH relative mass, anode gas (H2) flow rate of 0.1 L / min, and cathode gas (Air) flow rate of 0.2 L / min. Graphs plotting the current-voltage (IV) characteristics and power density were created from the measured current density and other parameters (Figures 8 and 9).
[0083] <Continuous Operation Evaluation Test> The electrodes of the PCFC fabricated as described above were evaluated for continuous operation at a cell temperature of 600°C. Under conditions of relative mass of 100%RH, anode gas (H2) flow rate of 1 L / min, and cathode gas (Air) flow rate of 2 L / min, the current density was 0.4 A / cm². 2 Continuous operation was performed for 300 hours to achieve the desired result. In Figure 10, the vertical axis shows the voltage.
[0084] <Measurement of the average film thickness and its standard deviation of the intermediate layer> For the electrodes of the PCFC fabricated as described above, the average film thickness and its standard deviation of the intermediate layer were measured. A scanning microscope (Hitachi, model SU8230) was used for these measurements. Three images were acquired at 2000x magnification using the SEM, and the film thickness dm was measured at five random locations in the intermediate layer of one of the images. The measurement results are shown in Table 2. Figures 6A to 6C are cross-sectional SEM images of the intermediate layer of the comparative example. In Figures 6A to 6C, the fuel electrode 530, solid electrolyte membrane 550, and intermediate layer 600 are stacked in this order in the comparative example. In the comparative example, the air electrode was delaminated from the intermediate layer 600 when the cross-section was acquired. Figures 7A to 7C are cross-sectional SEM images of the intermediate layer of the example. The film thickness shown in Table 2 was measured from each image.
[0085] [Table 2]
[0086] As shown in Table 2, in the comparative example, the average thickness of the intermediate layer was 1.00 μm, with a high standard deviation of 0.56. Therefore, an intermediate layer with uneven thickness was formed. In contrast, in the example, the average thickness of the intermediate layer was 0.83 μm, with a low standard deviation of 0.12. Therefore, there was less variation in thickness, and a uniform intermediate layer was formed. As shown in Figures 8 and 9, the initial IV characteristics of the example were improved compared to the comparative example. The maximum power density at a cell temperature of 600°C was 409 mW / cm². 2 (0.5V) to 488mW / cm 2 (0.55V) was improved. Also, as shown in Figure 10, the potential was unstable in the comparative example. As shown in Figure 11, in the example where the variation in the thickness of the intermediate layer was improved, the potential fluctuation was small and stable. [Explanation of Symbols]
[0087] 1. Proton-conducting ceramic fuel cell 30 Fuel electrode 40 Air pole 50 Solid electrolyte membrane 100 Middle Class 200 External channel 530 Fuel electrode 550 Solid electrolyte membrane 600 Middle layer Average film thickness at the Dc air electrode De Average thickness of solid electrolyte membrane Average thickness of the intermediate layer (Dm)
Claims
1. An electrode for a proton-conducting ceramic fuel cell, Air electrode containing cobalt (Co), A proton-conducting solid electrolyte membrane containing zirconium (Zr) and / or cerium (Ce) and barium (Ba), Fuel electrode and An intermediate layer formed between the air electrode and the solid electrolyte membrane, Equipped with, The aforementioned intermediate layer is It includes a perovskite-type oxide containing at least cerium (Ce) and barium (Ba), When the thickness of the intermediate layer in the stacking direction of the air electrode and the solid electrolyte membrane is measured at 15 or more locations, the average thickness is 0.5 μm or more and 5 μm or less. The standard deviation of the average film thickness is 0.3 μm or less. Electrodes for proton-conducting ceramic fuel cells.
2. The perovskite-type oxide contained in the intermediate layer is given by the following formula (3): (No) α3 A3 1-α3 ) x3 (C) β3 B3 1-β3 ) y3 O 3+δ3 (3) (Here, A3 is at least one selected from calcium (Ca), strontium (Sr), and lanthanum (La); B3 is at least one selected from zirconium (Zr), yttrium (Y), and ytterbium (Yb); α3 is 0.2 to 1; x3 is 0.8 to 1.2; β3 is 0.1 to 1.0; y3 is 0.8 to 1.2; and δ3 is -0.8 to 0.8.) The electrode according to claim 1, satisfying the requirements.
3. The solid electrolyte membrane is given by the following formula (4): (Ba α4 A4 1-α4 ) x4 (B4) β4 C4 1-β4 ) y4 O 3+δ4 (4) (Here, A4 is at least one selected from calcium (Ca), strontium (Sr), and lanthanum (La); B4 is at least one selected from zirconium (Zr) and cerium (Ce); C4 is at least one selected from yttrium (Y) and ytterbium (Yb); α4 is 0.2 to 1; x4 is 0.8 to 1.2; β4 is 0.1 to 1.0; y4 is 0.8 to 1.2; and δ4 is -0.8 to 0.8.) The electrode according to claim 1, comprising a proton-conducting oxide that satisfies the following conditions.
4. The electrode for a proton-conducting ceramic fuel cell according to any one of claims 1 to 3, wherein the intermediate layer is a porous material.
5. An inkjet printing ink used in the manufacture of electrodes for proton-conducting ceramic fuel cells, A powder of a perovskite-type oxide containing at least cerium (Ce) and barium (Ba), Dispersion medium and Includes, The perovskite-type oxide powder has an average particle size of 50 nm or more and 1000 nm or less, determined by laser diffraction and light scattering methods. The surface tension of the dispersion medium is 29 mN / m or less, in the ink.
6. When the total mass of the perovskite-type oxide powder and the dispersion medium in the ink is 100 mass%, The content of the perovskite-type oxide powder is 5 mass% or more and 30 mass% or less. The ink according to claim 5, wherein the content of the dispersion medium is 70 mass% or more and 95 mass% or less.
7. The ink according to claim 6, wherein the dispersion medium is composed of at least one selected from hexanol and diethylene glycol dibutyl ether.
8. A step of preparing an ink by mixing a perovskite-type oxide powder containing at least cerium (Ce) and barium (Ba) with a dispersion medium, A step of inkjet printing the ink onto the surface of a proton-conducting solid electrolyte film containing zirconium (Zr) and / or cerium (Ce) and barium (Ba), A step of forming an intermediate layer on the surface of the solid electrolyte film by sintering the ink, Includes, Here, when 20 μL of the ink is dropped onto the substrate, The contact angle θ is given by the following equation (5): θ=2tan -1 (] / r) (5) (Here, r is the radius of the surface of the water droplet in contact with the substrate, and h is the height from the substrate to the top of the water droplet.) A method for manufacturing electrodes for a proton-conducting ceramic fuel cell, satisfying the condition of 25° or less.
9. The method for producing an electrode according to claim 8, wherein the dispersion medium is composed of at least one selected from hexanol and diethylene glycol dibutyl ether.
Citation Information
Patent Citations
Electrode for proton-conducting ceramic cell, manufacturing method thereof, and proton-conducting ceramic cell using the same
JP2023006322A
Proton conduction ceramic cell
JP2024074357A
Electrode for proton conduction ceramic cells, manufacturing method thereof, and proton conduction ceramic cell using the same
JP2024090108A